Chrysotus Meigen (Diptera: Dolichopodidae) from Tibet with descriptions of four new species - Liu, Ruosi; Wang, Mengqing; Yang, Ding (Zootaxa, 2013)
The genus Chrysotus Meigen is reported from Tibet for the first time. Five species are recorded. The following four species are described as new to science: Chrysotus altavaginas sp. nov., C. motuoensis sp. nov., C. namaicunensis sp. nov. and C. tibetensis sp. nov. .Chrysotus biprojicienus Wei & Zhang is recorded from Tibet for the first time. A key to the species of Chrysotus from Tibet is presented.